INNOVATION DEVELOPMENT OF UKRAINE IN THE CONDITIONS OF TECHNOLOGY TRANSFER AND S&T COOPERATION - Medvedkin, Taras (Journal of European Economy, 2017)
The paper investigates the theoretical and practical aspects of the innovation activity in Ukraine in the context of international science and technology (S&T) cooperation.